The intellectual worldview of viceregal Peru prior to Independence - Vargas Ezquerra, Juan Ignacio (2009)
The viceroy of the time opted for a policy of conciliation and rapprochement with the American elites, especially the interests already granted by the Bourbon policy of the 18th century. His policy in Peru was not innovative, much less abrupt, but rather a continuation of a process of rapprochement —which had already begun— between the viceregal government and the Lima elites. The political skill of the Spaniard allowed him to survive in a potentially dangerous situation, in which the Lima elite, devious and intriguing as always, were looking for ways to promote their own interests. But the ebb of ideas also took place in the university cloisters of San Marcos and San Antonio, located in the two main Peruvian cities, Lima and Cusco, where scholastics and novatores debated as soon as works of L'Encyclopèdie were clandestinely read under the constant look, between condescending and attentive, of the Viceroy of Peru.